INTI KONFEDERASI WAJO: SURVEY ARKEOLOGI DI TOSORA, CINNOTABI AND LAMASEWANUA - Moh. Ali Fadillah; M. Irfan Mahmud; Budianto Hakim (WalennaE, 2020)
“The beginning of Wajo's establishment began with the migration of people from various places to open rice fields and build settlements to the east of Lake Tempe. The settlements were then transformed into political units which formed a 'state' under the rule of a nobleman based in Cinnotabi. Several political agreements underlie the formation of a confederation of three domains. Regime change resulted in the transfer of the center of government. Lontara Wajo and the oral tradition mention some toponyms but do not explain in detail where the core of the Wajo confederation lies. This research is aimed at determining the location and character of the toponym by conducting field surveys in places that are suspected of being associated with the existence of the pre-Islamic capital of Wajo. Using an archaeological approach and supported by information from textual sources. Surveys in the villages of Tosora, Cinnongtabi and Tajo in Majauleng District have identified the existence of the old capitals around Wajo-wajo, Boli, Leppadeppa, Attunuang, and other sites based on archeological traces such as menhirs, burned bone fragments, pottery and ceramics shards and other artifacts. Identification of imported ceramic fragments from China, Thailand, Vietnam, these sites might be dated between the 14th and 17th centuries. Taking into account the concentration of artefacts and relations between sites, it can be concluded that Tosora was the capital from the end of the 16th century and until the arrival of Islam at the beginning of the 17th century, while the capital of the early period of Wajo hypothetically was dated between the beginning of the 15th century and the end of the 16th century was around the confluence of Wajo-wajoe river which flows into Latamperu and Penrange lake which then empties into Cellue river before ending at the Cenrana mainstream”